2020
DOI: 10.1038/s42003-020-01455-6
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular lipid-binding domain of human Na+/H+ exchanger 1 forms a lipid-protein co-structure essential for activity

Abstract: Dynamic interactions of proteins with lipid membranes are essential regulatory events in biology, but remain rudimentarily understood and particularly overlooked in membrane proteins. The ubiquitously expressed membrane protein Na+/H+-exchanger 1 (NHE1) regulates intracellular pH (pHi) with dysregulation linked to e.g. cancer and cardiovascular diseases. NHE1 has a long, regulatory cytosolic domain carrying a membrane-proximal region described as a lipid-interacting domain (LID), yet, the LID structure and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 93 publications
1
8
0
1
Order By: Relevance
“…Finally, given the key role of anionic lipids including phosphatidyl-inositol(4,5)-diphosphate (PI[4,5]P 2 ) in regulating NHE1 by interacting with the C-tail ( Aharonovitz et al, 2000 ; Shimada-Shimizu et al, 2014 ), Ca 2+ -CaM could also regulate NHE1 through electrostatic tuning of the NHE1:PI(4,5)P 2 interaction. Such mechanisms are reported for several other membrane proteins ( Cao et al, 2013 ; Monteiro et al, 2014 ) and would be consistent with the folding of the NHE1-LID domain upon membrane interaction, bringing the CaM-binding region in close proximity to the NHE1-LID and the membrane ( Hendus-Altenburger et al, 2020 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, given the key role of anionic lipids including phosphatidyl-inositol(4,5)-diphosphate (PI[4,5]P 2 ) in regulating NHE1 by interacting with the C-tail ( Aharonovitz et al, 2000 ; Shimada-Shimizu et al, 2014 ), Ca 2+ -CaM could also regulate NHE1 through electrostatic tuning of the NHE1:PI(4,5)P 2 interaction. Such mechanisms are reported for several other membrane proteins ( Cao et al, 2013 ; Monteiro et al, 2014 ) and would be consistent with the folding of the NHE1-LID domain upon membrane interaction, bringing the CaM-binding region in close proximity to the NHE1-LID and the membrane ( Hendus-Altenburger et al, 2020 ).…”
Section: Discussionsupporting
confidence: 83%
“…Our results agree with earlier work showing that cellular NHE1:CaM interaction is partially retained in an NHE1 variant functionally similar to our H1-CR variant ( Bertrand et al, 1994 ). Additionally, cellular NHE1:CaM interactions may occur through C-tail interactions with other proteins (e.g., calcineurin) or membrane lipids ( Hendus-Altenburger et al, 2019 ; Hendus-Altenburger et al, 2020 ), independent of the residues studied here but also giving rise to PLA signals. Finally, while NHE1:CaM proximity in the absence of interaction cannot be excluded, the observed binding of NHE1 to apo-CaM in vitro and the lack of effect of ionomycin on the number of proximity events observed in cells indicate that a fraction of NHE1:CaM complexes are present at all times.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…N-терминальный трансмембранный домен много раз пересекает мембрану в обоих направлениях, поэтому характерным элементом его ВС является большое количество α-спиралей. Кроме того, несколько α-спиралей входят в состав Cтерминального цитозольного домена, находящегося вне мембраны [7].…”
Section: сокращенияunclassified
“…Recently, it has been suggested that NHE may increase susceptibility to SARS-CoV-2 and the severity of COVID-19 [ 5 , 6 ]. Interestingly, there is also an interaction between lipids and NHE [ 7 ]. Here, we examined whether there is a triple interaction between SARS-CoV-2, lipids, and NHE.…”
Section: Introductionmentioning
confidence: 99%